The Effect of Tianmai Xiaoke Pian on Insulin Resistance through PI3-K/AKT Signal Pathway - Nana Wang; Tiegang Li; Ping Han (Journal of Diabetes Research)
In the clinical setting, given the potential adverse effects of thiazolidinediones and biguanides, we often have difficulty in treatment that no other insulin sensitizers are available for use in type 2 diabetic mellitus (T2DM) patients. Tianmai Xiaoke Pian (TMXKP) is a traditional Chinese medicine tablet, which is comprised of chromium picolinate, Tianhuafen, Maidong, and Wuweizi. To understand its mechanism of action on insulin resistance, TMXKP (50 mg/kg orally) was tested in T2DM rats (induced by a high-fat diet and streptozotocin). Eight weeks later, fasting blood glucose (FBG) and oral glucose tolerance tests (OGTT) were performed. Area under the curve (AUC) and homeostatic model assessment of insulin resistance (HOMA-IR) were calculated, and PI3-K/AKT signal pathway-related genes and proteins were tested by reverse transcription-polymerase chain reaction (RT-PCR) and western blot analysis in muscle, adipose, and liver tissues, respectively. TMXKP significantly reduced FBG, OGTT, AUC, and HOMA-IR in diabetic rats P<0.05. Furthermore, we also observed that TMXKP could significantly decrease IRS-1, IRS-2, PI3-K p85α, and AKT2 gene expression and also IRS-1, IRS-2, PI3-K, AKT2, and p-AKT2 protein expression levels P<0.05 in diabetic rats. These findings confirm that TMXKP can alleviate insulin resistance in T2DM rats through the PI3K/AKT pathway. Thus TMXKP appears to be a promising insulin sensitizer.